Oil palm management by using aerial photography and ArcGIS software / Nabilah Ismail - Ismail, Nabilah (Faculty of Plantation and Agrotechnology, 2019)
Monitoring process for oil palm needed more precise innovation, cheap, fast and accurate technology. Before the existence of new technology, farmers used manual or traditional technique to manage their plantation area that is time and labour consuming. Remote sensing is one of the most reliable measurements tools for accurate monitoring and managing over large area. The purpose of this study is to count the oil palm tree in the plantation, to check the spacing distance between the oil palm trees and to monitor the status and obstacle in the oil palm plantation area. This study was conducted at Share Farm UiTM Jasin Melaka. Drone and Global Positioning System (GPS) were used to capture the oil palm area and to collect the coordinate of the oil palm tree. ArcGIS software 10.3 has been used in this procedure. The tree and the distance of the oil palm were measured. Based on the results, it shows that the oil palm tree area is unorganized because of some obstacles. The obstacles that has been observed is clogging water, which it resulted from the old water reservoir used to accumulate water for oil palm tree activity usage. A part from that, fallen trees and old tree is also considered as the barrier in the oil palm area. In conclusion, ArcGIS software facilitates farmers to monitor and manage their plantation field. Thus, Precision Agriculture can be recommended as a better alternative than the existing traditional method.